The effect of special training exercise on FGF21 expression and FGFR-1 among CABG patients - Bakhtiar, Sara; Barari, Alireza; Abdi, Ahmad (Researcher Bulletin of Medical Sciences, 2022)
Background: The aim of this study is to evalute special training exercise on the FGF21 and FGFR-1 among coronary artery bypass surgery (CABG) patients. Materials and Methods: The study method was semi-experimental and the statistical population was patients who had heart disease, after coronary artery bypass surgery. Results: The study results showed 8 weeks of special exercises among the experimental group had a significant increase in the expression levels of FGF21 and FGFR1 among CABG patients, compared to the control group. Physical activity may increase FGF21 levels, which is an important factor in oxidative stress and inflammation. Conclusion: The study results showed 8 weeks of special exercises among the experimental group had a significant increase in the expression levels of FGF21 and FGFR1 among CABG patients, compared to the control group. Physical activity may increase FGF21 levels, which is an important factor in oxidative stress and inflammation.